A Step Closer to the Electrochemical Production of Liquid Fuels. Issue 41 (31st July 2014) - Schouten, Klaas Jan P.; Calle‐Vallejo, Federico; Koper, Marc T. M.
<x xml:space="preserve">Abstract</x> Fueled by success: A nanostructured copper electrocatalyst derived from copper oxide can reduce carbon monoxide to multicarbon oxygenates, including ethanol. This is an important step in the production of liquid fuel by the reduction of CO2 using electricity from renewable sources.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>